PEMBUATAN PULP DENGAN MEMANFAATKAN LIMBAH KULIT DURIAN (DURIO ZIBETHINUS MURR) DENGAN CAMPURAN (RESINA COLOPHONIUM) GUNA MENCEGAH DEGRADASI LINGKUNGAN - Kurniawan W, Deddy Kurniawan W; Arifan, Fahmi; Adim, M. Dwi Khoirun (Gema Teknologi, 2013)
Deddy Kurniawan W, Fahmi Arifan, M. Dwi Khoirun Adim, in this article explain that paper is one of the primary needs for humans today . High paper usage is resulting increased in production of paper . On the other hand, paper which are usually made ​​from cellulose and hemi-cellulose in wood can result environmental degradation , due to the use of wood and tree felling leads to long-term basis that can increase the temperature of the earth surface ( global warming) . Durian is relatively abundant in Indonesia , durian shell contains high cellulose ( 50-60 % ) and lignin content ( 5 %), also  a low starch content ( 5 % ) . Durian shell wastes containing fibre  with dimensions of length and fiber thick wall that be able to bind well when given a synthetic adhesive or an adhesive mineral . Pulp which is produced from durian shell waste in experiments were 1 , 2 , 3 and 4, have a value of α - cellulose content of 35 % , 45 % , 27.7 % , 37.5 % and 57.6 %, respectively. When yield value of  49.2 % , 66.8 % and 48.2 % respectively. Keywords: pulp, durian, gondorukem, digester